RopB protein of Rhizobium leguminosarum bv. viciae adopts amyloid state during symbiotic interactions with pea (Pisum sativum L.) - Kosolapova, Anastasiia O.; Belousov, Mikhail V.; Sulatsky, Maksim I.; Tsyganova, Anna V.; Sulatskaya, Anna I.; Bobylev, Alexander G.; Shtark, Oksana Y.; Tsyganov, Viktor E.; Volkov, Kirill V.; Zhukov, Vladimir A.; Tikhonovich, Igor A.; Nizhnikov, Anton A. (Frontiers in Plant Science, 2022)
Amyloids represent protein aggregates with highly ordered fibrillar structure associated with the development of various disorders in humans and animals and involved in implementation of different vital functions in all three domains of life. In prokaryotes, amyloids perform a wide repertoire of functions mostly attributed to their interactions with other organisms including interspecies interactions within bacterial communities and host-pathogen interactions. Recently, we demonstrated that free-living cells of Rhizobium leguminosarum, a nitrogen-fixing symbiont of legumes, produce RopA and RopB which form amyloid fibrils at cell surface during the stationary growth phase thus connecting amyloid formation and host-symbiont interactions. Here we focused on a more detailed analysis of the RopB amyloid state in vitro and in vivo, during the symbiotic interaction between R. leguminosarum bv. viciae with its macrosymbiont, garden pea (Pisum sativum L.). We confirmed that RopB is the bona fide amyloid protein since its fibrils exhibit circular x-ray reflections indicating its cross-β structure specific for amyloids. We found that fibrils containing RopB and exhibiting amyloid properties are formed in vivo at the surface of bacteroids, and undifferentiated cells of R. leguminosarum extracted from pea nodules. Moreover, using pea sym31 mutant we demonstrated that formation of extracellular RopB amyloid state occurs at different stages of bacteroid development but is enhanced in juvenile symbiosomes. Proteomic screening of potentially amyloidogenic proteins in the nodules revealed the presence of detergent-resistant aggregates of different plant and bacterial proteins including pea amyloid vicilin. We demonstrated that preformed vicilin amyloids can cross-seed RopB amyloid formation suggesting for probable interaction between bacterial and plant amyloidogenic proteins in the nodules. Taken together, we demonstrate that R. leguminosarum bacteroids produce extracellular RopB amyloids in pea nodules in vivo and these nodules also contain aggregates of pea vicilin amyloid protein, which is able to cross-seed RopB fibrillogenesis in vitro. Thus, we hypothesize that plant nodules contain a complex amyloid network consisting of plant and bacterial amyloids and probably modulating host-symbiont interactions.